2009
DOI: 10.1080/00150190902987749
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric and Elastic Properties of γ-Irradiated Gadolinium Calcium Oxoborate, GdCa4O(BO3)3, Single Crystal

Abstract: O(BO 3 ) 3 (GdCOB), single crystal caused by γ -irradiation were investigated.The crystal was exposed to γ -radiation of a dose up to 2 MGy. The changes in frequencies of piezoelectric resonances were registered with variation of the dose for two crystal plates: (XY) and (ZX) vibrating in longitudinal modes. The relationship between the radiation dose and the elastic coefficients s E 11 , s E 22 as well as the piezoelectric coefficients d 31 , d 12 was found. GdCOB crystal can be recommended for application in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Generally, harsh environments accompanying high temperature include low pO2 atmospheres, vacuum, high pressure/corrosive steam, high level of radiation, etc., thus it is essential to investigate the electrical properties of high temperature piezoelectric materials under those conditions. It has been reported that hard γ radiation has limited effects on GdCOB crystals at room temperature, thus oxyborate crystals are projected to be used for structural health monitoring of the nuclear reactors at high dose irradiation of >10 5 Gy . However, studies need to be performed on crystals under the combination of high temperature, hard irradiation, and corrosive environments, to better understand the reliability and stability of the piezoelectric materials under practical operational conditions.…”
Section: Future Workmentioning
confidence: 99%
“…Generally, harsh environments accompanying high temperature include low pO2 atmospheres, vacuum, high pressure/corrosive steam, high level of radiation, etc., thus it is essential to investigate the electrical properties of high temperature piezoelectric materials under those conditions. It has been reported that hard γ radiation has limited effects on GdCOB crystals at room temperature, thus oxyborate crystals are projected to be used for structural health monitoring of the nuclear reactors at high dose irradiation of >10 5 Gy . However, studies need to be performed on crystals under the combination of high temperature, hard irradiation, and corrosive environments, to better understand the reliability and stability of the piezoelectric materials under practical operational conditions.…”
Section: Future Workmentioning
confidence: 99%
“…They are widely used in lasers and nonlinear and piezoelectric fields and are optoelectronic functional materials with excellent performance. [7][8][9][10][11][12] Among the REECOB crystals, research on GdCa 4 O(BO 3 ) 3 and YCa 4 O(BO 3 ) 3 crystals is significant and has never stopped. The Yb:YCOB crystal was reported to realize 10.1 W continuous wavelength laser output at 1085 nm.…”
Section: Introductionmentioning
confidence: 99%
“…A high-temperature environment generally accompanies many other challenging conditions, for example, low pO 2 and hard irradiation etc. The sensors must withstand not only the high temperatures (usually >650 °C) but also irradiation or low oxygen partial pressures. Although different prototype piezoelectric sensors have been designed based on ReCOB (Re: Y and Gd) crystals, ,, the stabilities of the electroelastic properties under high-energy heavy ion irradiation conditions have not been investigated in detail. Thus, it is desired to understand the performance of piezoelectric materials under hard irradiations.…”
Section: Introductionmentioning
confidence: 99%